Metal toxicity and opportunistic binding of Pb(2+) in proteins - Kirberger, Michael (2013)
Lead toxicity is associated with various human diseases. While Ca(2+) binding proteins such as calmodulin (CaM) are often reported to be molecular targets for Pb(2+)-binding and lead toxicity, the effect of Pb(2+) on the Ca(2+)/CaM regulated biological activities cannot be described by the primary mechanism of ionic displacement (e.g., ionic mimicry). The focus of this study was to investigate the mechanism of lead toxicity through binding differences between Ca(2+) and Pb(2+) for CaM, an essential intracellular trigger protein with two EF-Hand Ca(2+)-binding sites in each of its two domains that regulates many molecular targets via Ca(2+)-induced conformational change. Fluorescence changes in phenylalanine indicated that Pb(2+) binds with 8-fold higher affinity than Ca(2+) in the N-terminal domain. Additionally, NMR chemical shift changes and an unusual biphasic response observed in tyrosine fluorescence associated with C-terminal domain sites EF-III and EF-IV suggest a single higher affinity Pb(2+)-binding site with a 3-fold higher affinity than Ca(2+), coupled with a second site exhibiting affinity nearly equivalent to that of the N-terminal domain sites. Our results further indicate that Pb(2+) displaces Ca(2+) only in the N-terminal domain, with minimal perturbation of the C-terminal domain, however significant structural/dynamic changes are observed in the trans-domain linker region which appear to be due to Pb(2+)-binding outside of the known calcium-binding sites. These data suggest that opportunistic Pb(2+)-binding in Ca(2+)/CaM has a profound impact on the conformation and dynamics of the essential molecular recognition sites of the central helix, and provides insight into the molecular toxicity of non-essential metal ions.